Level of social adjustment and educational adjustment among high school students in grades 11-16 in Sulaimani city center - حمە, ئەحمەد على (Sulaimani Journal for Humanities, 2019)
The adolescence stage is a critical stage in human life, where it witnesses many major changes, which reflects and affects other stages of life, so it’s very sensitive and needs accurate detaoils to conduct researches in order to understand and aware of changes and needs of adults in that stage of life. The aim of this research is to determine the social adaption level among students of 10th and 11th class of preparatory schools at Suleimanyah City, also to determine the educational adaption level among students of 10th and 11th class of preparatory schools at at Suleimanyah City, the difference of social adaption level and educational adaption of male and female students, in addition to knowing the relationship between the social and educational adaption level among students of 10th and 11th classes of preparatory schools at Suleimanyah city. The resrarcher has used analytical descriptive method for this study, in order to adapt this method with subjects and facts that the researcher tried to show and prove. The study society consists of the entire students of preparatory classes at Suleimanyah city, total of (37.345) students, (16.700) male students and (20.645) female students. The study sample consists of (233) students of both 10th and 11th preparatory classes both male and female,total of (112) students are female and (121) of them are male. For the purpose of achieving research objectives, the researcher had studied set of criteria, previous researches and tools that the research conducted with, the researcher then prepared a standard consisting of (36) paragraphs to measure the social adaptation and 34 paragraphs to measure the educational adaption. The research results showed that the level of social adaption for students of both sexes was at an average level. The adaption level of education among 10th and 11th preparatory class’s students was at an average level, Gender had no impact on social and educational adaption has an impact on social adaption. Finally some recommendations and propositions that would be benefice have been put forward.